N-Glycans on the Nipah Virus Attachment Glycoprotein Modulate Fusion and Viral Entry as They Protect against Antibody Neutralization - Biering, Scott B. (American Society for Microbiology, 2012)
Nipah virus (NiV) is the deadliest known paramyxovirus. Membrane fusion is essential for NiV entry into host cells and for the virus' pathological induction of cell-cell fusion (syncytia). The mechanism by which the attachment glycoprotein (G), upon binding to the cell receptors ephrinB2 or ephrinB3, triggers the fusion glycoprotein (F) to execute membrane fusion is largely unknown. N-glycans on paramyxovirus glycoproteins are generally required for proper protein conformational integrity, transport, and sometimes biological functions. We made conservative mutations (Asn to Gln) at the seven potential N-glycosylation sites in the NiV G ectodomain (G1 to G7) individually or in combination. Six of the seven N-glycosylation sites were found to be glycosylated. Moreover, pseudotyped virions carrying these N-glycan mutants had increased antibody neutralization sensitivities. Interestingly, our results revealed hyperfusogenic and hypofusogenic phenotypes for mutants that bound ephrinB2 at wild-type levels, and the mutant's cell-cell fusion phenotypes generally correlated to viral entry levels. In addition, when removing multiple N-glycans simultaneously, we observed synergistic or dominant-negative membrane fusion phenotypes. Interestingly, our data indicated that 4- to 6-fold increases in fusogenicity resulted from multiple mechanisms, including but not restricted to the increase of F triggering. Altogether, our results suggest that NiV-G N-glycans play a role in shielding virions against antibody neutralization, while modulating cell-cell fusion and viral entry via multiple mechanisms.